Pengaruh Disiplin Kerja dan Prestasi Kerja terhadap Kinerja Pegawai Negeri Sipil pada Kantor Badan Pendapatan Daerah Kota Denpasar - Sota Raditya Permana, I Gede; Sri Hartati, Ni Putu; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Performance has a very important role because performance is the final result of the civil servant's process of completing their duties. To improve the performance of civil servants, work discipline and high job satisfaction are needed. The aim of this research is to determine the influence of work discipline and work performance on the performance of civil servants at the Denpasar City Regional Revenue Agency Office. This research was conducted at the Denpasar City Regional Revenue Agency with a population of 60 civil servants. This research uses census techniques so that all members of the population are involved as research subjects. Primary data collection was carried out using a questionnaire. Hypothesis testing is carried out using multiple linear regression. Based on the results of the analysis, it can be concluded that: 1) work discipline has a positive and significant effect on employee performance, 2) work performance has a positive and significant effect on employee performance, 3) work discipline and work performance has a positive and significant effect on employee performance.